Solvent-free solid-phase synthesis method of titanium silicalite molecular sieve TS-1
Through the solvent-free solid phase synthesis method, titanium silicon molecular sieve TS-1 is synthesized in a closed container using mechanical force-assisted rotary reactor, which solves the problems of long time in hydrothermal reaction, large solvent consumption and environmental pollution, and obtains high quality and high quality Efficient molecular sieve material, suitable for industrial applications.
Patent Information
- Application Number
- CN202310796396.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2024-12-31
AI Technical Summary
In the prior art, the synthesis process of titanium silicon molecular sieve TS-1 has problems such as complicated operation, difficult conditions to control, many non-skeleton titanium formation, long hydrothermal reaction time, large consumption of solvents and template agents, and serious environmental pollution, which affects catalysis. Performance and industrial applications.
Using solvent-free solid phase synthesis method, the titanium source, silicon source and organic alkali template agent are mixed in a closed container through mechanical force assisted rotating reactor, and the application of mechanical force is applied to promote solid phase crystallization, reduce the use and reaction time of template agent, and improve the Crystalline degree and surface area.
The preparation of high-quality titanium silicon molecular sieve TS-1 in a short time has been achieved, reducing the equipment pressure resistance requirements, production costs and environmental pollution, and improving production efficiency and catalytic performance.
Smart Images

Figure CN119219014A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a solvent-free solid phase synthesis method of titanium silicate molecular sieve TS-1, belonging to the field of chemistry and chemical engineering. Background Art
[0002] TS-1 molecular sieve is a microporous molecular sieve with MFI topological structure. 4+ Center, so it has a good catalytic effect on the selective oxidation reaction of organic matter with the participation of H2O2, such as epoxidation of olefins, hydroxylation of phenol, ammoximation of ketones, oxidation of alkanes, etc. The catalytic oxidation process of TS-1 molecular sieve is pollution-free and the reaction conditions are mild, which overcomes the shortcomings of serious pollution and lengthy reaction process in traditional processes.
[0003] The synthesis of TS-1 was first reported by Taramasso et al. (US4410501). The synthesis used tetraethyl silicate (TEOS) as the silicon source, tetraethyl titanate (TEOT) as the titanium source, and tetrapropylammonium hydroxide (TPAOH) as the template, and was obtained by hydrothermal crystallization at 130-200°C in an autoclave for 6-30 days. However, this method is cumbersome to operate, the conditions are difficult to control, the experimental repeatability is poor, and due to the difference in the hydrolysis rate of the silicon source and the titanium source, a large amount of non-framework titanium is formed, which affects the catalytic performance of the TS-1 molecular sieve. Subsequently, Thangaraj et al. (zeolite, 12 (1992), 943) obtained the TS-1 molecular sieve with less non-framework titanium by pre-hydrolyzing ethyl orthosilicate in a TPAOH aqueous solution, and then slowly adding an isopropanol solution of tetrabutyl titanate with a slower hydrolysis rate under vigorous stirring. These improvements are mainly to control the hydrolysis process of silicon source and titanium source, so that the hydrolysis rates of silicon source and titanium source are more matched, inhibit the formation of non-framework titanium, and increase the framework titanium content in TS-1 molecular sieve.
[0004] In the prior art, the synthesis of molecular sieves mainly uses a hydrothermal synthesis system, and the feed liquid has fluidity limitations, especially for solid raw materials, there is a technical prejudice that it is difficult to synthesize. Therefore, the prior art often uses more solvents and organic base templates, which has high costs and subsequent environmental protection problems. In addition, the process of hydrothermal synthesis of molecular sieves in the prior art has a long reaction time and low efficiency, which is not conducive to the high-efficiency needs of industrial industrial development. Summary of the invention
[0005] According to one aspect of the present application, a solvent-free solid-phase synthesis method of titanium silicate molecular sieve TS-1 is provided, which utilizes mechanical force to assist the solid-phase synthesis of molecular sieves, thereby solving the problems of long production time, large consumption of solvents and templates, and subsequent generation of wastewater in the preparation of molecular sieves by hydrothermal reaction in the prior art, while still being able to obtain high-quality, high-crystallization, and high-specific surface area molecular sieve materials that are equivalent to or better than the molecular sieves obtained by the hydrothermal reaction method in the prior art.
[0006] This application adopts the following technical solutions:
[0007] A method for solvent-free solid phase synthesis of titanium silicate molecular sieve TS-1 comprises the following steps:
[0008] A mixture containing a titanium source, a silicon source, an organic base template and a grinding material is placed in a closed container and continuously rotated for solid phase crystallization to obtain the titanium silicon molecular sieve TS-1.
[0009] The grinding material provides additional mechanical force to the molecular sieve raw materials during the synthesis process
[0010] Optionally, the molar ratio of the titanium source, the silicon source, and the organic base template is (0.005-0.1):1:(0.01-10);
[0011] Wherein, the molar number of the titanium source is calculated as the molar number of TiO2;
[0012] The mole number of the silicon source is calculated as the mole number of SiO2;
[0013] The molar number of the organic base template agent is based on the molar number of N atoms in the organic base template agent;
[0014] Optionally, the molar ratio of the titanium source, the silicon source, and the organic base template is (0.01-0.08):1:(0.05-5).
[0015] Optionally, the molar ratio of the titanium source to the silicon source is selected from any value of 0.005:1, 0.008:1, 0.01:1, 0.02:1, 0.03:1, 0.04:1, 0.05:1, 0.06:1, 0.07:1, 0.08:1, 0.09:1, 0.1:1, or any range between the two, wherein the molar ratio of the titanium source is AlO 3 / The molar number of the silicon source is measured by the molar number of SiO2.
[0016] Optionally, the molar ratio of the silicon source and the organic base template is selected from any value of 1:0.01, 1:0.02, 1:0.05, 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:1, 1:2, 1:3, 1:4, 1:5, 1:8, 1:10, or any range between two values, wherein the molar number of the template is calculated based on the molar number of N atoms in the template; the molar number of the silicon source is calculated based on the molar number of SiO2.
[0017] Optionally, the rotation speed is 1 rpm to 80 rpm.
[0018] Optionally, the rotation speed during the molecular sieve synthesis process is selected from any value of 1 rpm, 5 rpm, 10 rpm, 20 rpm, 30 rpm, 40 rpm, 50 rpm, 60 rpm, 70 rpm, 75 rpm, 80 rpm, or any range therebetween.
[0019] Optionally, the conditions for the solid phase crystallization are: a crystallization temperature of 100 to 200° C., and a crystallization time of less than or equal to 168 h.
[0020] Optionally, the material of the grinding material is selected from at least one of agate, aluminum oxide, zirconium oxide, stainless steel, and synthetic resin.
[0021] Optionally, the grinding material has a shape selected from at least one of a sphere, a rod, a cube, a triangular pyramid, and a star.
[0022] Optionally, the organic base template comprises A;
[0023] The A is selected from at least one of a quaternary ammonium salt or a quaternary ammonium base.
[0024] Optionally, A is selected from at least one of tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, triethylpropylammonium hydroxide, tetrapropylammonium halide, tetraethylammonium halide, tetrabutylammonium halide, and triethylpropylammonium halide.
[0025] Optionally, the organic base template further comprises B;
[0026] The B is selected from at least one of aliphatic amines and alcohol amine compounds.
[0027] Optionally, B is selected from at least one of ethylamine, diethylamine, triethylamine, n-butylamine, butanediamine, hexamethylenediamine, octanediamine, monoethanolamine, diethanolamine and triethanolamine.
[0028] Optionally, the titanium source is selected from at least one of tetraethyl titanate, tetrabutyl titanate, tetraisopropyl titanate, and titanyl sulfate.
[0029] The silicon source is selected from at least one of silica sol, ethyl orthosilicate, methyl orthosilicate and white carbon black.
[0030] Optionally, the conditions for the solid phase crystallization are: a crystallization temperature of 100 to 130° C., and a crystallization time of 1 to 6 hours.
[0031] The method for synthesizing titanium silicalite TS-1 proposed in this application can shorten the preparation time, improve product quality and reduce chemical waste, etc. It can effectively reduce the use of templates and solvents in traditional hydrothermal synthesis processes, and is particularly suitable for solid-phase synthesis processes.
[0032] Optionally, the solid phase crystallization temperature is selected from any value of 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, or any range therebetween.
[0033] Optionally, the solid phase crystallization time is selected from any value of 1h, 6h, 12h, 24h, 48h, 72h, 96h, 120h, 144h, 168h, or any range therebetween.
[0034] Optionally, the method for solvent-free solid phase synthesis of titanium silicalite TS-1 is:
[0035] A mixture consisting of a titanium source, a silicon source, an organic base template and a grinding material is placed in a closed container and continuously rotated for solid phase crystallization to obtain the titanium silicon molecular sieve TS-1.
[0036] Optionally, the closed container is a rotary reactor device.
[0037] In the present application, the rotary reactor device is used as a mechanically assisted rotary reaction device.
[0038] The steps of the method for synthesizing titanium silicon molecular sieve TS-1 using a rotary reactor device are as follows:
[0039] Titanium source, silicon source and organic base template are added into the rotating reactor through the feed port, and grinding material is added into the reactor. After sealing, the temperature is increased and the reactor is rotated by a motor. The grinding material continuously applies mechanical force to the synthetic raw materials during the rotation process. After the reaction is completed, the molecular sieve product is poured out through the discharge port.
[0040] The technical solution of the present application is a solvent-free solid-phase synthesis method of titanium silicate TS-1. No solvent is used or the use of solvent is greatly reduced in the process of synthesizing the molecular sieve. During the synthesis of the titanium silicate TS-1 molecular sieve, the grinding material exerts mechanical force on raw materials such as silicon source, titanium source and template agent. Different from the traditional hydrothermal reactor, the technical solution of the present application utilizes rotation and grinding materials to introduce mechanical force to promote the nucleation and crystal growth of the molecular sieve.
[0041] The beneficial effects of the present invention include: Solvent-free solid phase synthesis method of titanium silicate TS-1
[0042] 1) The method of the present application is to synthesize titanium silicalite TS-1 under solvent-free solid phase conditions with the assistance of mechanical force, and the molecular sieve material can be prepared in a relatively short time.
[0043] 2) The method for solvent-free solid-phase synthesis of titanium silicalite TS-1 in the present application has a low autogenous pressure of the reaction system and a low pressure resistance requirement for the equipment. At the same time, the solid-phase system can reduce the use of templates and does not require solvents, which can reduce production costs in terms of process and raw materials, improve production efficiency, and effectively reduce environmental pollution. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 This is a scanning electron microscope image of the product synthesized in Example 1 of this application.
[0045] Figure 2 This is the X-ray powder diffraction image of the product synthesized in Example 1 of the present application.
[0046] Figure 3 This is a scanning electron microscope image of the product synthesized in Example 2 of this application.
[0047] Figure 4 This is the X-ray powder diffraction image of the product synthesized in Example 2 of this application. DETAILED DESCRIPTION
[0048] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0049] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0050] The analysis method in the examples of this application is as follows:
[0051] In the examples of the present application, the SEM morphology analysis of the product was performed using a Hitachi SU8020 scanning electron microscope.
[0052] In the examples of the present application, the X-ray powder diffraction phase analysis (XRD) of the product was performed using an X'Pert PRO X-ray diffractometer from PANalytical of the Netherlands, with a Cu target, a Kα radiation source (λ=0.15418 nm), a voltage of 40 KV, and a current of 40 mA.
[0053] According to one embodiment of the present application, a method for mechanical solvent-free solid phase synthesis of titanium silicalite TS-1 is operated, characterized in that the method comprises the following steps:
[0054] The raw materials of the molecular sieve to be synthesized: titanium silicon source, organic base template, silicon source, etc. are mixed in a certain proportion to obtain a solid phase mixture. Preferably, the solid phase mixture has the following molar ratio:
[0055] TiO2:SiO2=0.005~0.1:1;
[0056] Organic base template: SiO2 = 0.01 ~ 10: 1;
[0057] The silicon content in the silicon source is calculated based on the molar number of SiO2, the titanium content in the titanium source is calculated based on the molar number of TiO2; and the content of the organic base template is calculated based on the molar number of N atoms.
[0058] The solid phase mixture is added to a rotating reactor, and grinding materials are added to the reactor. The materials of the grinding materials include one or more mixtures of materials such as agate, aluminum oxide, zirconium oxide, stainless steel or synthetic resin. The shapes of the grinding materials include one or more mixtures of different shapes such as spheres, rods, cubes, triangular pyramids or stars. After sealing, the temperature is increased and rotated. During the reaction, the speed is between 1rpm and 80rpm, the temperature of the rotating reactor is between 100℃ and 200℃, and the molecular sieve synthesis time crystallization does not exceed 7 days. The grinding material continuously applies mechanical force to the synthetic raw materials during the rotation process, and the molecular sieve product is poured out through the discharge port after the reaction is completed.
[0059] Example 1
[0060] In this embodiment, 60g of tetraethyl orthosilicate, 5g of tetrabutyl titanate, and 15g of tetrapropylammonium hydroxide were placed in a molecular sieve synthesis container; agate grinding beads were added to the reaction system, and the reaction was carried out at a temperature of 170°C, a rotation speed of 40rpm, and a reaction time of 1 day to synthesize the titanium silicon molecular sieve TS-1 product.
[0061] Example 2
[0062] 30g of silica sol, 5g of tetraethyl titanate, and 15g of tetrabutylammonium hydroxide were placed in a molecular sieve synthesis container, and zirconium oxide and aluminum oxide grinding rods were added to the reaction system. At a temperature of 120°C, a rotation speed of 70rpm, and a reaction time of 6 hours, titanium silicalite molecular sieve TS-1 product was synthesized.
[0063] Example 3
[0064] 60g of fumed silica, 3g of tetraisopropyl titanate, and 25g of octanediamine were placed in a molecular sieve synthesis container; stainless steel ground triangular pyramids were added to the reaction system, and the titanium silicate molecular sieve TS-1 product was synthesized at a temperature of 200°C, a rotation speed of 20rpm, and a reaction time of 72 hours.
[0065] Embodiments 4 to 13
[0066] The specific ingredient types, materials and synthesis conditions are shown in Table 1 below. The synthesis equipment and other operations during the synthesis process are the same as those in Example 1.
[0067] Table 1 Molecular sieve synthesis conditions of Examples 4-13
[0068]
[0069]
[0070] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A method for solvent-free solid phase synthesis of titanium silicalite TS-1, characterized in that: The steps include: A mixture containing a titanium source, a silicon source, an organic base template and a grinding material is placed in a closed container and continuously rotated for solid phase crystallization to obtain the titanium silicon molecular sieve TS-1.
2. The method according to claim 1, characterized in that The molar ratio of the titanium source, the silicon source and the organic base template is (0.005-0.1):1:(0.01-10); Wherein, the molar number of the titanium source is calculated as the molar number of TiO2; The mole number of the silicon source is calculated as the mole number of SiO2; The molar number of the organic base template agent is based on the molar number of N atoms in the organic base template agent; Preferably, the molar ratio of the titanium source, the silicon source, and the organic base template is (0.01-0.08):1:(0.05-5).
3. The method according to claim 1, characterized in that The rotation speed is 1 rpm to 80 rpm.
4. The method according to claim 1, characterized in that: The conditions for the solid phase crystallization are: a crystallization temperature of 100 to 200° C., and a crystallization time of less than or equal to 168 hours.
5. The method according to claim 1, characterized in that The material of the grinding material is selected from at least one of agate, aluminum oxide, zirconium oxide, stainless steel, and synthetic resin; Preferably, the shape of the grinding material is selected from at least one of sphere, rod, cube, triangular pyramid and star.
6. The method according to claim 1, characterized in that The organic base template agent includes A; The A is selected from at least one of a quaternary ammonium salt or a quaternary ammonium base; Preferably, A is selected from at least one of tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, triethylpropylammonium hydroxide, tetrapropylammonium halide, tetraethylammonium halide, tetrabutylammonium halide and triethylpropylammonium halide.
7. The method according to claim 1, characterized in that The organic base template further comprises B; The B is selected from at least one of aliphatic amines and alcohol amine compounds; Preferably, B is selected from at least one of ethylamine, diethylamine, triethylamine, n-butylamine, butanediamine, hexamethylenediamine, octanediamine, monoethanolamine, diethanolamine and triethanolamine.
8. The method according to claim 1, characterized in that The titanium source is selected from at least one of tetraethyl titanate, tetrabutyl titanate, tetraisopropyl titanate, and titanyl sulfate; The silicon source is selected from at least one of silica sol, ethyl orthosilicate, methyl orthosilicate and white carbon black.
9. The method according to claim 1, characterized in that: The conditions for the solid phase crystallization are: a crystallization temperature of 100 to 130° C. and a crystallization time of 1 to 6 hours.
10. The method according to claim 1, characterized in that The method is: A mixture consisting of a titanium source, a silicon source, an organic base template and a grinding material is placed in a closed container and continuously rotated for solid phase crystallization to obtain the titanium silicon molecular sieve TS-1.
Citation Information
Patent Citations
Synthesis method of TS-1 titanium silicalite molecular sieve
CN107162013A
Synthesis method of Ti-MWW molecular sieve
CN108557840A
Method for synthesizing TS-1 zeolite through size-adjustable solvent-free method
CN112875717A
Method for solvent-free solid-phase synthesis of molecular sieve
CN119219013A